PENERAPAN FUZZY EXPERT SYSTEM UNTUK DIAGNOSA PENYAKIT TELINGA, HIDUNG DAN TENGGOROKAN (THT) - Muhammad Yunus (MATRIK : Jurnal Manajemen, Teknik Informatika dan Rekayasa Komputer, 2015)
Otorhinolaryngology is a group of diseases that infect many people including Indonesians, especially in West Lombok Regency in West Nusa Tenggara. This disease is very dangerous because it disrupts the respiratory area such as polyp and sinusitis in the nose.This research is discuss about the making of expert system by fuzzy logic concept to diagnose the otolaryngology. The amount of otolaryngology that used to be sample for this research is 18 type of disease which consisted of 10 diseases in ear, 5 diseases in nose and 3 diseases in throat. While the patients who used to be test cases are 50 people. Inference system method that used in this research is Mamdani with deffuzifcation process by centroid method. From the results of the test system with the number of patients of 50 people, the results concluded that the level of match between the application result and doctor’s diagnosis achieve an accuracy of 82% for this type of disease analysis. As many as 64,85% of the 82% of the application test data are in accordance with the doctor’s analysis namely disease’s name and degree 34,15% of them match the disease’s name but there is a difference between the applications values with doctor’s analysis. Trial data that do not match doctor’s analysis is 18%.